2014
DOI: 10.1111/jce.12385
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Fluoroscopy Use in Catheter Ablation Procedures: Six Years of Experience at a Single Center

Abstract: RF catheter ablation of SVT with an approach completely guided by the NavX system and without use of fluoroscopy is feasible, safe, and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 20 publications
5
26
0
1
Order By: Relevance
“…The feasibility of eliminating x-ray use altogether by using a 3D mapping system was demonstrated in a relatively small pediatric study showing a 95% reduction in fluoroscopy time with 24 of 30 patients requiring no fluoroscopy whatsoever 29 . The "near-zero" radiation objective has been achieved in subsequent studies using the NavX system for all steps of the procedure instead of fluoroscopy, other than in a variety of arrhythmias, also for atrioventricular nodal reentry tachycardia 30 , 31 .…”
Section: Typical Atrial Fluttermentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of eliminating x-ray use altogether by using a 3D mapping system was demonstrated in a relatively small pediatric study showing a 95% reduction in fluoroscopy time with 24 of 30 patients requiring no fluoroscopy whatsoever 29 . The "near-zero" radiation objective has been achieved in subsequent studies using the NavX system for all steps of the procedure instead of fluoroscopy, other than in a variety of arrhythmias, also for atrioventricular nodal reentry tachycardia 30 , 31 .…”
Section: Typical Atrial Fluttermentioning
confidence: 99%
“…In this series, ablation success rate was 95% and no complications occurred. A more recent study reported on the systematic use of a a nonfluoroscopic approach in a larger cohort of 328 patients 35 . This group consisted of 35 patients with AVRT whereas patients with left sided accessory pathway or those who needed a transeptal puncture were excluded from the study.…”
Section: Atrioventricular Re-entrant Tachycardia Reciprocating Atriomentioning
confidence: 99%
“…While mapping systems are extremely useful in the treatment of these complex conditions, in the last 15 years some studies have demonstrated that they can also be applied to CA of simple arrhythmias [4,6,10,15,16]. The use of mapping systems in these cases does not compromise the treatment or make it less effective in comparison with traditional CA.…”
Section: Discussionmentioning
confidence: 98%
“…4–7,913,1519 Kühne et al advocate using transesophageal echocardiography (TEE) prior to TSP access, 10 whereas several groups describe intra-procedural TEE-guided TSP access with a high degree (97–100%) of AF-free event rates during respective follow-up periods. 13,16,17 Other groups have described TEE-guided TSP in combination with fluoroscopy to minimise radiation exposure, however reported outcomes from this approach demonstrated comparatively reduced AF-free success rates (75–85%).…”
Section: Discussionmentioning
confidence: 99%